INSPIRING TEACHERS FROM THE SPECTACLES OF STUDENTS AT MAN 1 BARRU - Azizah, Nur Wafiq; Samtidar, Samtidar; Korompot, Chairil Anwar (JTechLP: Journal of Technology in Language Pedagogy, 2024)
This research aimed to identify the characteristics of Inspiring Teachers in the Spectacles of Students. This research used a quantitative method. The sample in this research were students of class X.1 and XI MIPA 1 Madrasah Aliyah Negeri 1 Barru. This class was selected as participants using cluster random sampling techniques. This research instrument used a questionnaire using Skala Likert techniques to determine the characteristics of Inspiring Teachers. Overall, all students strongly agreed with these characteristics, the highest score was 3.63 and the lowest score was 3, 32. where the average score on each question is above 3.25, which means it falls into the strongly agree category and three characteristics are most often chosen by students, namely 1) inspiring teachers have broad-minded characteristics with the highest score of 3.63. 2) conveying learning in a fun way so that learning in class is not boring with the highest score of 3.61. 3) Inspirational teachers can provide new insights and directed and meaningful learning for students with the highest score of 3.60. Therefore, it can be concluded that the characteristics of inspiring teachers based on experts are highly approved by MAN 1 Barru students.